Análisis de flujo de carga en el sistema de distribución eléctrico basado en cadenas de Markov - Alarcón Villegas, Jairo Mauricio (2017)
The purpose of this document is analyze the load variation that exists in an electric power system by increasing the demand for electric energy consumption, supplying representative loads such as: electric cars and induction cookers connected to the distribution system; The analysis is done by means of the stochastic method of "MARKOV CHAINS" a discrete time and space of continuous states, which defines the possible states of operation as is the connection and disconnection of the loads for a determined period of 24 hours, in The analysis of results shows the variation of load for each half hour of consumption. To determine these results, the mathematical simulation software "MATLAB" is used, in which the flow of power is solved by means of the "Newton Raphson" algorithm and the electric power is optimized. Of the simulation with its relevant graphs supporting the case studies proposed in this document. For the pertinent purposes, the twelve-bar power system of the "IEEE" has been taken as a reference, on which the load variation of the system will be worked on.